Analysis of Income Convergence in G-20 Countries with Structural Break Unit Root Test - Ertugrul, Mustafa Emre; Tanrıseven, Kemaletttin (International Journal of Economics and Financial Issues, 2018)
In the globalizing world, the convergence of countries can't be avoided. Any phenomenon in a country can reach other countries within a short period of time. Therefore, the article was made by using G - 20 countries that came together for a purpose. The article also analysis whether or not the real income per capita of the countries can converge over time. The sample period is between 1960 and 2016. Considering the possibility of breaking during this period in the time series, the study was also tested with the single fractured Lee-Strazicich (2013) Unit Root Test. Keywords: G-20 Countries; Convergence; Lee-Strazicich (2013) Unit Root Test JEL Classifications: C22; C41